2015
DOI: 10.1177/1098300715580992
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between School-Wide Positive Behavior Interventions and Supports and Academic, Attendance, and Behavior Outcomes in High Schools

Abstract: Attendance, behavior, and academic outcomes are important indicators of school effectiveness and long-term student outcomes. Multi-tiered systems of support (MTSS), such as School-Wide Positive Behavior Interventions and Supports (SWPBIS), have emerged as potentially effective frameworks for addressing student needs and improving student outcomes. Much of the research on SWPBIS outcomes has taken place at the elementary and middle school levels, leaving a need for a more thorough examination of outcomes at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 26 publications
4
104
1
5
Order By: Relevance
“…Experimental studies have not found any effect of SWPBS on academic achievement (Benner et al, ; Bradshaw et al, ; Horner et al, ), while quasi‐experiments have reported mixed effects (Caldarella, Shatzer, Gray, Young, & Young, ; Freeman et al, ; Gage et al, ; Gage, Leite, Childs, & Kincaid, ; Lane, Wehby, Robertson, & Rogers, ; Madigan et al, ). However, small sample sizes and a short research period (Madigan et al, ) limit the validity of the outcomes.…”
Section: Previous Research On Swpbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have not found any effect of SWPBS on academic achievement (Benner et al, ; Bradshaw et al, ; Horner et al, ), while quasi‐experiments have reported mixed effects (Caldarella, Shatzer, Gray, Young, & Young, ; Freeman et al, ; Gage et al, ; Gage, Leite, Childs, & Kincaid, ; Lane, Wehby, Robertson, & Rogers, ; Madigan et al, ). However, small sample sizes and a short research period (Madigan et al, ) limit the validity of the outcomes.…”
Section: Previous Research On Swpbsmentioning
confidence: 99%
“…There has been growing concerns regarding bullying, and positive school‐wide prevention efforts such as SWPBS has been suggested as an effective intervention to reduce bullying (Waasdorp et al, ). Academic outcomes are, together with behaviour and attendance, important indicators of school effectiveness (Freeman et al, ).…”
Section: The Present Studymentioning
confidence: 99%
“…Still, there have been some studies that evaluated data over time that did not find significant positive relationships between SWPBIS and academic outcomes (e.g., Caldarella, Shatzer, Gray, Young, & Young, ; Freeman et al, ). However, some of these studies did not comprehensively consider implementation fidelity, which refers to the degree to which the core features of SWPBIS are implemented exactly as they are designed and intended.…”
Section: Outcomes Associated With Pbismentioning
confidence: 99%
“…This is problematic considering the research that has found positive associations between implementation fidelity and positive academic and behavioral student outcomes (Marin & Filce, ; Pas & Bradshaw, ; Simonsen et al, ). Some of the studies that did not find a significantly positive relationship between SWPBIS and academic achievement either did not consistently measure implementation fidelity (e.g., Caldarella et al, ) or categorized or dichotomized implementation fidelity variables (e.g., Freeman et al, ; Gage, Sugai, Lewis, & Brzozowy, ; Noltemeyer et al, ), which limits the variability within these fidelity measures and also makes it more difficult to detect small changes in implementation. Thus, future research can treat any implementation fidelity measure as a continuous variable to fully evaluate its impact on academic achievement.…”
Section: Outcomes Associated With Pbismentioning
confidence: 99%
“…For example, SWPBIS implementation has been associated with improved academic skills, attendance, social behavior, and appropriate behavior for students in general (Freeman et al, 2015) The universal supports provided within SWPBIS have been documented as being beneficial for students at-risk or at high risk for aggressive behavior, difficulty concentrating, and emotional regulation (Bradshaw, Waasdorp, & Leaf, 2015). To date, over 23,000 schools implement SWPBIS (OSEP Technical Assistance Center on Effective School-Wide Interventions, 2017).…”
Section: Schoolwide Positive Behavioral Interventions and Supports (Smentioning
confidence: 99%